Differentiation of aroma compositions in different regions and special varieties of black tea - Xu Yuanjun; He Jing; Jia Lingyan; Wu Yuanyuan; Tu Youying (浙江大学学报. 农业与生命科学版, 2015)
Aroma of tea is an important factor determining the quality. There were many studies on the analysis of different kinds of tea's aroma, but most of them didn't discuss the difference between different teas. The aroma of floral type black tea and black tea with higher amino acid was very special, and neither of them has been studied before.The aroma compositions of five kinds of traditional black tea, three kinds of floral type black tea and four kinds of black tea with higher amino acid, were analyzed using solid-phase microextraction/gas chromatography-mass spectrometry (SPME/GC-MS) in different black tea samples comparatively.Results showed that 75 kinds of aromatic components were detected, and 26, 19, 34, 30, 17, 29, 34, 23, 20, 16, 20 and 24 kinds of aroma substances from Yunnan congou black tea, Qimen congou black tea, Yichang black tea, Yinde black tea, Shuangfeng black tea, Panyong congou black tea, Jinguanyin black tea, Huangguanyin black tea, Zhuhai Golden tea, Jinyuxian black tea, Huangjinya black tea, Hengsheng black tea. The ingredients for the characteristic aroma of black tea were mainly ascertained to be alcohols, esters and hydrocarbons. The linalool, linalool oxide, geraniol, benzyl alcohol, phenethyl and methyl salicylate were the characteristic aroma substances of black tea.In conclusion, the results and related literature provide the specificity of different regions and special varieties of black tea, with the preliminary discussion on the causes of the aroma. The nerolidol, α-farnesene and indole are higher in floral type black tea, which are the characteristic aroma in oolong tea. The nitrogenous compounds are higher in the aroma of high amino acid black tea, such as 2-acetylpyrrole and quinoline.